The Trend in the Prevalence of Diabetes Mellitus in the Mexican Indigenous Population From 2000 to 2018 - Lilia V. Castro-Porras, ScD; Rosalba Rojas-Martínez, PhD; Martín Romero-Martínez, PhD; Carlos A. Aguilar-Salinas, PhD; Consuelo Escamilla-Nuñez, ScD (Elsevier, 2023)
Introduction: Diabetes is a worldwide public health problem. In Mexico, diabetes was the third leading cause of death in the total population in 2020. The indigenous people in Mexico are approximately 6%. This study aims to estimate the trends in diabetes prevalence from 2000 to 2018 in the group of Mexican indigenous language speakers and to analyze the main sociodemographic (e.g., age, educational and socioeconomic level, and the urbanicity of the area of residence) and clinical (e.g., age of diabetes onset, years with diabetes, and BMI) characteristics of this group. Methods: This cross-sectional study included participants aged ≥20 years from 4 National Health Surveys, 2000-2018. We presented the analyses for indigenous and nonindigenous strata. Logistic models adjusted were used to estimate the trend of diabetes in the study period. Results: We found a significant increase in the prevalence of diabetes in the indigenous group. This trend in the ORs was maintained when adjusting for age, sex, waist circumference, and area of residence. For the study period, the prevalence change in diagnosed diabetes in the indigenous group was greater than that in the nonindigenous group (OR=6.4, 95% CI=4.1, 8.8 and OR=3.3, 95% CI=2.5, 4.1, respectively). We also found a significant prevalence change in undiagnosed diabetes for the indigenous group (OR=7.7, 95% CI=1.3, 14.6). Conclusions: In contrast to the results in nonindigenous populations, our main result reveals an increasing probability of being diabetic in the indigenous population from 2006 to 2018. It is necessary to clarify the origin of the accelerated change in diabetes prevalence among the indigenous population in Mexico.